Transcranial direct current stimulation of motor cortex enhances spike performances of professional female volleyball players - Park, S. B.; Han, D. H.; Hong, J.; Lee, J.-W. (Journal of Motor Behavior, 2023)
The purpose of this study was to investigate effects of brain excitability by transcranial direct current stimulation (tDCS) on spike performances of professional female volleyball players. Thirteen professional female volleyball players were recruited for participation. We performed a randomized single-blind, SHAM-stimulus controlled, and counter-balanced crossover design with two interventions in this study. An anodal tDCS current was applied over the primary motor cortex (M1) for 20 min at 2 mA. In the SHAM intervention, the current was first applied for 30 s, after which it was terminated. Exercise performance assessment which comprised spike performance (spike ball speed, spiking consistency), two vertical jumps (jump and reach: JaR, countermovement jump: CMJ), bench-press and back-squat one-repetition maximum (1RM) were tested pre- and post-intervention. Results indicated that spike ball speed and spiking consistency following tDCS were significantly higher than those after SHAM intervention (both p < 0.05). However, JaR and CMJ did not show any significant differences between tDCS and SHAM intervention groups (both p > 0.05). There was no significant difference in bench-press and back-squat 1RM between two groups either (both p > 0.05). These findings suggest that tDCS could be effective in enhancing motor coordination performances of professional female volleyball athletes.